Intellectual abilities among survivors of childhood leukaemia as a function of CNS irradiation. Issue 5 (May 1978) - Eiser, C
Abstract : Twenty-eight children in remission at least 2 years after completing chemotherapy for acute lymphoblastic leukaemia were assessed on standardised psychological tests. It was found that 7 who never had central nervous system (CNS) irradiation and 9 having prophylactic CNS irradiation at least 6 months after diagnosis tended to perform at average or above levels, while those 10 each having prophylactic CNS irradiation (within 2 months of diagnosis) were generally of lower ability. Within the latter group, 3 children showed serious intellectual impairments, while the group as a whole functioned especially poorly on quantitative tasks and those involving speeded performance with abstract material. General language ability was not affected. Practical and theoretical implantation are discussed.